Experimental Investigation on Flow Past an Isolated Micro Pin Fin Embedded in a Microchannel. Issue 1 (2nd January 2022) - Ji, Can; Liu, Zhigang; Lv, Mingming; Li, Jichao
ABSTRACT: Micro pin fin heat sink is a very attractive cooling technique for high power density microelectronics. Optimization of its cooling performance requires insightful understanding on fundamental physics of flow inside it, especially around a single pin fin. In the present study, an experimental investigation on flow past an isolated low aspect ratio (height-to-diameter ratio) pin fin embedded in a microchannel is conducted using Micro-PIV. The flow field and vorticity distribution at different channel heights under various Reynolds numbers are obtained. Endwall effect is found to play an important role in flow past the pin fin in the microchannel, and the critical Reynolds numbers are larger than that at the conventional scale. Vorticity concentrations are formed on both sides of the pin fin along the shear layer and intensify with the increase in Reynolds number. Flow fields and vorticity distributions at different heights exhibit different characteristics, especially at higher Reynolds numbers, indicating three-dimensionalities of the flow. Viscous resistance of the endwalls leads to lower overall velocity, smaller extent of the recirculation zone and weaker vorticity in flow layer closer to the top and bottom channel walls. Pressure drop and flow resistance characteristics in the microdevice is analyzed. The effect of aspect ratio of the pin fin on the wake flow is also studied, and the results show that three-dimensionalities increase but critical Reynolds numbers decrease with larger aspect ratios. A comparison with flow across micro pin fin arrays is conducted and differences are observed in velocity field and wake flow features.